Intravitreal Ranibizumab Had Limited Effect on Cystoid Macular Edema Due to Albumin-Bound Paclitaxel: A Case Report and Literature Review - Ye, Suna; Fang, Qiqi; Yao, Jinyu; Xing, Jianqiang; Tang, Shibo; Ma, Jacey Hongjie (Frontiers in Oncology, 2021)
Angiographically silent cystoid macular edema (CME) is a rare complication from nab-paclitaxel. Here we report a 45-year-old woman with breast cancer who developed CME after several months of treatment with albumin-bound paclitaxel (nab-paclitaxel). Her visual acuity did not improve significantly with the cessation of nab-paclitaxel and intravitreal ranibizumab treatment. Then, brinzolamide eye drops were prescribed. One month later, her vision improved, with the macular edema significantly subsided. Finally, we reviewed other cases of CME induced by nab-paclitaxel that have been reported in the literature and discussed the underlying pathogenesis of nab-paclitaxel-induced CME.